ICT integration in the educational system of Philippines - Tomaro, Queenie Pearl Villalon (Universitas Muhammadiyah Yogyakarta, 2018)
Purpose - The paper aims highlight the state of ICT integration to the educational system of the Philippines, including the challenges, efforts, and possible solutions. Design/Methodology/Approach - The study is a review of two scholarly works focusing on the case of ICT integration in the educational system of Philippines. The paper reviewed were the paper of Kubota, Yamamoto, and Morioka (2018) entitled, Promoting ICT education in developing countries: Case Study in the Philippine and the research work of Bonifacio (2013) entitled, Developing Information Communication Technology (ICT) Curriculum Standards for K-12 Schools in the Philippines. Findings - The critical analysis of the reviewed papers revealed several policy actions to fully integrate ICT in education in the case of Philippines such as added trainings for teachers, provision of computer infrastructures, integration of ICT in the curriculum in a strategized manner, and lastly a strong leadership. Originality - The paper provided a lens both on the problematic situation on the actual school set-ups and also the possible key steps to be undertaken for improvement. It is a review of the selected academic papers which delves into the ICT-Integration in the Educational System of Philippines. The formal efforts of the government were also highlighted including the prime importance of ICT in education. The paper does not only embolden a problem of the inadequacy of the school facilities but it highlights how this problem affects the competitiveness of Filipinos in the job market and the backwardness of the standing of the country in technological advancement.